CRITICAL ANALYSIS OF PANCHABHOOTHA SIDHANTHA - K.P.Roshni (International Journal of Applied Ayurved Research, 2016)
Panchamahabhoota Siddhanta (principle of five elements) is considered to be one of the principles of Indian philosophy, which explains the integrity of all the living and non- living substances in this universe. Panchamahabhootas (principle of five elements) can be seen in two ways in philosophies -As a part of cosmogenesis and a part of Dravya (Matter). The reason to understand the origin of the universe is that, the source of Mahabhautika (gross elements) evolution lies in it and to understand this concept as a whole, one has to understand its base. So it is mandatory for us to know the things which are using in our practice, from where they are originated.The basic principles of Ayurveda though genuine and of much utility, its analysis and implementation need more research.